Linear maps preserving the Cullis determinant of (n+1)× n matrices - Guterman, Alexander; Yurkov, Andrey (Sarajevo Journal of Mathematics, 2024)
In this paper we give an explicit description of linear maps preserving the Cullis determinant of rectangular matrices of the size (n+1)× n. Unlike the result about the ordinary determinant, it appears that linear preservers of Cullis determinant can be singular. We provide the corresponding examples and characterize the case when these maps are non-singular.